Regionale Polarisierung der demographischen Entwicklung in Ostdeutschland — Gleichwertigkeit der Lebensverhältnisse? - Herfert, Günter (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
The paper addresses the new demographic patterns of spatial development which have arisen in eastern Germany since early 2000; it also analyses the underlying demographic structures. These extremely differentiated quantitative analyses are based on data from the municipalities on population development, and more particularly on the nexus of migration viewed in terms of selected structural features. The author explores the extent to which, following the wave of suburbanisation in the 1990s, the landscape of eastern Germany — characterised by demographic shrinkage — is now marked by tendencies of regional polarisation, ranging from signs of reurbanisation to wider-scale deconcentration. In this respect, this paper augments previous analyses conducted at the pan-German level with a perspective which is distinctly on eastern Germany. The paper closes with a discussion of the current debate on visions (or “leitbilder”) for spatial development in Germany based on the results of the analysis, and finally considers some issues related to maintaining parity of living conditions throughout Germany.